Buckling and post-buckling of steel box section using finite element method - Isham, Nur Hazwani (2021)
Typically components of structural member use combination of plate structures (i.e. plate elements) in many engineering applications. Many of these structures are subjected to in-plane compressive loading. During compression, the load increases while the stiffness maintained until it reaches the critical load whereby the out-of-plane deflections start to visible. As the load increases, the stiffness reduces to half of its pre-buckling stiffness and the deflections growth in stable manner. This is accompanied by continues alterations in the stress distributions within the cross section. It is therefore important to study the buckling and post-buckling behavior of such components. Most of the studies of square box-section struts in compression have been focusing on constant uniform thickness. This is due to the sections manufactured, available in the market and the standard used by the manufactures to form the sections. All square and rectangular sections have been formed with wall thickness uniform around the section. Nevertheless, it is possible to form the square box-sections with different thickness ratios. This gives more flexibility in design and reduce wastages. The research work sets out an investigation on behavior of the stress distributions of the plates and box section in the post-buckling region with regards to varying thickness ratios of the box section which are 1mm and 2mm. It was observed that the stress variations of box section with thickness ratio 1:1 and plate with thickness 1mm are similar while the stress variations of box section with thickness ratio 1:2 and plate with thickness 2mm are significantly different. A detailed account of the growth and redistributions of stresses across the section was given in the research work. The results from the finite element simulations were shown to compare well with the analytical method of analysis. The percentage difference of the numerical value for square plate model in this study was less than 10% when comparing with the theoretical value.